Revesz syndrome revisited - Karremann, Michael; Neumaier-Probst, Eva; Schlichtenbrede, Frank; Beier, Fabian; Brümmendorf, Tim Henrik; Cremer, Friedrich Walter; Bader, Peter; Dürken, Matthias (Orphanet journal of rare diseases, 2020)
Revesz syndrome (RS) is an extremely rare variant of dyskeratosis congenita (DKC) with only anecdotal reports in the literature.